ENGINEERING STAFF TRAINING WITH CONSIDERATION OF MODERN ECONOMIC SCIENCE ACHIEVEMENTS - G. P. Litvintseva; N. G. Nizovkina; N. A. Gakhova (Russian State Vocational Pedagogical University, 2017)
Introduction. Achievements in various fields of modern science have an impact not only on the development of science itself, but also on the formation of human capital, including training of technical personnel needed for the transition to an information society.The aim of the article is to show interinfluence of different sciences of engineering staff training and specific aspects of their training in modern conditions.Methodology and research methods. The research is based on the system-based approach, experimental knowledge generalization, comparative analysis and economics methodology. We used analysis of national and foreign literature, official documents and statistic data of the Russian Federation, Global Competitiveness Index. Also, information processing was carried out using graphic methods.Results. The influence of natural sciences on economic knowledge development as well as on perfection of engineering and engineering education is shown. Decrease in researcher numbers as well as lack of young people in engineering sciences is revealed. In particular, the following disturbing facts are established and emphasized: engineers are a fifth part among graduates and this share has been nearly constant during the last 10 years. However, the number of engineering specialists going abroad for work continues to grow.Scientific novelty. The conclusions on the influence of natural sciences on economic theory development as well applied economics on engineering development are made. Special aspects of modern engineers training as knowledge integrator are highlighted.Practical significance. Based on the analysis of official statistics, data the trend of engineering specialists decrease in Russia is shown. In connection with engineering staff aging and low number of engineering companies, the necessity for new engineering model implementation and new type of engineers training is emphasized.